Photographing prisoners: the unworthy, unpleasant and unchanging criminal body - Miranda, Diana (Criminology & criminal justice, 2019)
The use of photography in representing the criminal body has long been a focus of interest in the social sciences, especially so when exploring the historical evolution of criminal identification practices. By contributing to the emerging field of visual criminology, this article explores current practices around photography of prisoners in the everyday contexts of the prison space. Drawing on a qualitative study conducted with prisoners, prison guards and probation officers in three Portuguese prisons, we analyse how different social actors construct the criminal body. This construction is explored through the meanings attributed to prisoners’ photographic portraits used for their identification. In particular, we discuss how their photographic documentation acts as a classification device and a visual representation of the criminal. We argue that this representation, by portraying elements of unworthiness, unpleasantness and immutability, plays a significant role in the parole board’s decisions and produce an embodied sense of identity and perpetuation of stigma.